Microbial itaconic acid production from starchy food waste by newly isolated thermotolerant Aspergillus terreus strain - Narisetty, Vivek; Prabhu, Ashish A.; Al-Jaradah, Khalid; Gopaliya, Deeksha; Hossain, Abeer H.; Khare, Sunil Kumar; Punt, Peter J.; Kumar, Vinod (Elsevier, 2021)
In the present study, we have explored the potential of newly isolated Aspergillus terreus BD strain, which can accumulate itaconic acid (IA) at higher temperature. The shake flask cultivation of thermotolerant strain with medium optimized using Box-Behnken Design at 45 °C resulted in IA accumulation of 28.9 g/L with yield of 0.27 g/g. The enzymatic saccharification of the synthetic food waste (SFW) consisting of potatoes, rice & noodles were optimized using Taguchi method of orthogonal array to maximize the release of fermentable sugar. The maximum glucose release of 0.60 g/g was achieved with 10% biomass loading, 5% enzyme concentration, pH 5.5 and temperature 60 0C. The sugars obtained from SFW was integrated with IA production and maximum IA titer achieved with SFW hydrolysate during bioreactor cultivation was 41.1 g/L with conversion yield of 0.27 g/g while with pure glucose IA titer and yield were 44.7 g/L and 0.30 g/g, respectively.
Keywords: Enzymatic hydrolysis; Synthetic Food waste; Thermotolerant; Itaconic acid; Aspergillus terreus